Basal cell carcinoma of the prostate with squamous metaplasia: A case report and literature review - Wang, Junwei; Zhang, Cunming; Chen, Baijun; Wu, Qingqing (Frontiers in Oncology, 2023)
Basal cell carcinoma of the prostate (BCCP) is a rare tumor with a total incidence of 140 cases to date. However, BCCP with squamous metaplasia has not been reported as of date. In this paper, we report the first case of BCCP with squamous metaplasia. The patient was hospitalized for progressive dyspareunia and had been treated for recurrent urinary retention four times in 5 years. Rectal examination showed that the prostate was medium in texture with no palpable nodules. The levels of total prostate specific antigen (tPSA), free prostate specific antigen (fPSA), and fPSA/tPSA (f/t) ratio were 1.29 ng/mL, 0.4 ng/mL, and 0.31, respectively. Ultrasound of the urinary tract showed that the prostate gland was 51 mm*40 mm*38 mm in size. We performed transurethral resection of the prostate. Histopathology confirmed the diagnosis of basal cell carcinoma with focal squamous differentiation, and immunohistochemical staining was positive for P63 and 34βE12. A laparoscopic radical prostatectomy was performed 45 days after the first surgery and the postoperative pathology showed a small amount of residual tumor with negative margins and no involvement of the seminal vesicles and vas deferens. The patient was followed up for 50 months and was doing well by the end of our study. We describe the clinical symptoms, pathological features, treatment, and prognosis of patients with BCCP with squamous metaplasia. The relevant published literature is also briefly reviewed.